2019
DOI: 10.1016/j.mjafi.2018.11.007
|View full text |Cite
|
Sign up to set email alerts
|

A study of hepatitis A virus seropositivity among children aged between 1 and 5 years of age: Implications for universal immunization

Abstract: Background: Hepatitis A virus (HAV) causes an enterically transmitted viral disease mainly affecting children and endemic in many developing countries, including India. There is an epidemiological shift with an increased incidence of symptomatic cases among children.This study was conducted to assess the seroprevalence of HAV among young children aged below 5 years and the need for universal immunization.Method: This cross-sectional study was conducted at two tertiary care hospitals in Northern India, from Apr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…In this study, we found that a previous history of hepatitis A vaccination was significantly associated with HAV seropositivity among our participants. This finding was similar to a cross-sectional study in India, a lower-middle-income country, which revealed that hepatitis A vaccination, together with parental education levels, source of water supply, and history of jaundice, were the significantly associated factors of HAV seropositivity among their Indian children aged between 1 and 5 years 26 . We also found that overweight status was significantly correlated with seropositivity of HAV in our participants, particularly among unvaccinated individuals.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we found that a previous history of hepatitis A vaccination was significantly associated with HAV seropositivity among our participants. This finding was similar to a cross-sectional study in India, a lower-middle-income country, which revealed that hepatitis A vaccination, together with parental education levels, source of water supply, and history of jaundice, were the significantly associated factors of HAV seropositivity among their Indian children aged between 1 and 5 years 26 . We also found that overweight status was significantly correlated with seropositivity of HAV in our participants, particularly among unvaccinated individuals.…”
Section: Discussionsupporting
confidence: 88%
“…8 In India, the antibodies to HAV are found in more than 90% of adults; however, limited information is available on anti-HAV among children. 9 Hepatitis A is a vaccine-preventable disease and typically has an abrupt onset following an incubation period of approximately 28 days (range: 15 to 50 days). Signs and symptoms of infection can include nausea, vomiting, diarrhea, dark urine, jaundice, fever, headache, weight loss, and abdominal pain, as well as a loss of desire for cigarette smoking or alcohol.…”
Section: Introductionmentioning
confidence: 99%
“…Population-based seroprevalence surveys provide evidence for public health policy decisions, especially where mass vaccination and health-care worker protection are indicated, which need to be taken pragmatically, after due cost-effectiveness and cost-benefit analyses. In this issue of the journal, Kushwaha et al 17 and Gupta et al 18 have separately reported upon H1NI seroprevalence and hepatitis A virus (HAV), respectively, and commented on vaccination. With climate change happening since our yesterday, we have to accept that we will increasingly see the resurgence and emergence of diseases, with some vaccine protectable, most not.…”
mentioning
confidence: 99%